Proses Persidangan Perkara Perdata Berdasarkan Peraturan Mahkamah Agung (PERMA) Nomor 1 Tahun 2019 Tentang Administrasi Perkara dan Persidangan di Pengadilan Secara Elektronik - Virgie Diva Syahran; Ronald Saija; Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The e-Court system was created as a form of service for the community, especially justice seekers in terms of accommodating the online case settlement process.Purposes of the Research: To find out how the procedures for implementing e-Court are in accordance with applicable rules and whether or not there are obstacles in the implementation of this system, especially in the Ambon District Court. Methods of the Research: This research is a normative legal research supported by empirical data in the form of facts needed in the field, with a descriptive analytical research type, as well as legal materials which include primary legal materials, secondary legal materials and tertiary legal materials. The collection of legal materials is carried out through interviews and literature studies, which are descriptive and analytical in nature.his research is a normative legal research with analytical descriptive nature.Results of the Research: The results of this study, namely, first, that E-Court is a way to expedite the proceedings in the Court, as regulated in the principles of justice according to Supreme Court Regulation Number 1 of 2019 concerning Case Administration and Trial in Electronic Courts. Second, the electronic Court introduced by the Supreme Court allows several stages of the process in the Court to be carried out online. Third, the implementation of the e-Court system has various obstacles, one of which is the lack of public counseling and information regarding the application of this system, and there are still advocates who have not been verified or registered.